Screening and Analysis of Anaplasma marginale Tunisian Isolates Reveal the Diversity of lipA Phylogeographic Marker and the Conservation of OmpA Protein Vaccine Candidate - Belkahia, Hanène; Ben Abdallah, Meriem; Andolsi, Rihab; Selmi, Rachid; Zamiti, Sayed; Kratou, Myriam; Mhadhbi, Moez; Darghouth, Mohamed Aziz; Messadi, Lilia; Ben Said, Mourad (Frontiers in Veterinary Science, 2021)
Bovine anaplasmosis caused by Anaplasma marginale is a disease that may cause great economic losses worldwide. Thereby, the identification of A. marginale isolates from various bioclimatic areas in each country, the phylogeographic analysis of these isolates based on the most informative markers and the evaluation of the most promising candidate antigens are crucial steps in developing effective vaccines against a wide range of A. marginale strains. In order to contribute to this challenge, a total of 791 bovine samples from various bioclimatic areas of Tunisia were tested for the occurrence of A. marginale DNA through msp4 gene fragment amplification. Phylogeographic characterization was done through lipA and sucB gene analysis, and the genetic relationship with previously characterized A. marginale isolates and strains were analysed by applying similarity comparison, and phylogenetic analysis. To evaluate the conservation of OmpA protein vaccine candidate, almost complete ompA nucleotide sequences were also obtained from Tunisian isolates and various bioinformatic softwares were used in order to analyze the physicochemical properties, and the secondary and tertiary structures of their deduced proteins, and predict their immunodominant epitopes of B and T cells. Anaplasma marginale DNA was detected in 19 bovine samples (2.4%). Risk factors’ analysis shows that cattle derived from sub-humid bioclimatic area were more infected than those originated from other areas. The analysis of lipA phylogeographic marker indicated a higher diversity of Tunisian A. marginale isolates compared to other available worldwide isolates and strains. Molecular, phylogenetic and immuno-informatics analyses of the vaccine candidate OmpA protein demonstrated that this antigen and their predicted immunodominant epitopes of B and T cells appear to be highly conserved between Tunisian isolates and compared to isolates from other countries suggesting that the minimal intraspecific modifications will not affect the potential cross protective capacity of humoral and cell-mediated immune responses against multiple A. marginale worldwide strains.